Treating the locoregional lymph nodes with radiation and/or surgery significantly improves outcome in dogs with high‐grade mast cell tumours. (29th October 2019) - Mendez, Susan E.; Drobatz, Kenneth J.; Duda, Lilian E.; White, Pamela; Kubicek, Lyndsay; Sorenmo, Karin U.
Abstract: High‐grade canine mast cell tumours (HG‐MCT) have a high rate of locoregional relapse. In this study, dogs with HG‐MCT treated with radiation therapy (RT) were retrospectively evaluated to determine the benefit associated with treating the locoregional lymph nodes (LNs). Forty‐two dogs were included. Variables assessed for association with overall survival (OS) and progression‐free survival (PFS) included WHO stage, tumour location and size, LN irradiation (prophylactic, therapeutic or none), LN treatment (yes or no), LN status at RT (metastatic or nonmetastatic) and RT intent (definitive vs palliative). Lower‐stage disease at irradiation was significantly associated with prolonged median PFS (425 vs 125 days for stage 0 vs 1‐4), and OS (615 vs 314 days for stage 0 vs 1‐4). Having any LN treatment and definitive RT were both significantly associated with prolonged OS. In order to evaluate the role of LN irradiation, dogs were divided into subgroups: (a) stage 0 at irradiation with no LN treatment (n = 14), (b) stage 0 at irradiation with prophylactic LN irradiation (n = 6), (c) stage 0 at irradiation but previously stage 2 (n = 5) and (d) stage >0 at irradiation (n = 17). Prophylactic LN irradiation significantly prolonged PFS (>2381 vs 197 days; group B vs A). Interestingly, dogs that were stage 2 and had LN treatment (C) had prolonged OS vs dogs with negative LNs and no LN treatment (A) (1908 vs 284 days; P = .012). This study confirms that prophylactic and therapeutic LN irradiation in dogs with HG‐MCT is beneficial and improves outcome.